Incidence rate of third molar impaction cases during a two-quarter period in patients at the Dental Clinic of the Baturiti II Community Health Centre in Tabanan: Angka insiden kasus impaksi molar 3 selama periode dua triwulan pada pasien di Poli Gigi UPTD Puskesmas Baturiti II Tabanan - Kusuma, Dewa Indra; Idaryati, Ni Putu; Ariani, Ni Luh Putu (Makassar Dental Journal, 2025)
Third molar impaction is one of the most common dental and oral health problems encountered in primary health care services such as community health centres. This article reports the incidence of third molar impaction cases based on age and gender during a two-quarter period in patients at the dental clinic of the Baturiti II Community Health Centre in Tabanan. This descrip-tive study used secondary data from the E-Puskesmas system. The total number of visitors to the dental clinic of the Baturiti II Tabanan Community Health Centre during this period was 985, and the number of impaction cases was 32, resulting in a preva-lence of 3.24%. Based on gender, impaction cases were more common in females (59.3%) than males. Meanwhile, based on age, the 20-44 age group had the highest prevalence (81.25%). It was concluded that young adults and females have a higher risk of third molar impaction.